ITINERANT UNITY FOR TOMATOES HANDLING PROCESS - TEIXEIRA, RICARDO RODRIGUES; Sverzut, Cláudio Bianor (Revista Brasileira de Engenharia de Biossistemas, 2008)
The tomato post harvest losses can achieve high levels and it is proportional to the period the fruitis exposed to atmosphere in between harvest and handling. In this context, this study propose thedevelopment of a an itinerant unity to make the handling process of tomatoes within the field tryingto diminish the time between harvest and handling in order to reduce post harvest losses. To doso, it was identified, at field, the processes and tasks needed to make the tomato handling processtaking as base an itinerant unity. The unit was built in a wagon of a truck. All the costs relating tothe wagon building and operational process were analyzed. The itinerant unity proved itself as arelatively cheap solution to reduce the pos harvest losses in the tomato cultivating process.